Theoretical and methodological provision of justification of the enterprise activity efficiency in the marketing aspect - Iastremska, Olena; Gerasymov, Oleksandr (Technology audit and production reserves, 2020)
The object of research is the process of determining the main directions of improving the efficiency of the enterprise in the marketing aspect, that is taking into account both the peculiarities of its internal environment and market participants, that is the external environment. One of the problems is the insufficient consideration of the modern conceptual apparatus of efficiency. In addition, it is important in some cases to narrow the purpose of the project without taking into account the marketing aspect. An obstacle may be the difficulty of developing a list of criteria for selecting responsible project executors. It is often incomplete to take into account the strategic and current problems of improving the efficiency of the enterprise in the marketing aspect. Proposals for clarifying the definition of «efficiency» and «marketing aspect», the use of a project approach that takes into account the two main components of efficiency are substantiated and developed. These include: objective in the use of resource potential of enterprises and subjective, which takes into account the peculiarities of information and communication and marketing interaction of market participants. These components of efficiency allowed to eliminate the identified shortcomings of the studied problem. The main result of research is a substantiated and proposed content and sequence of stages of methodological support for determining areas for improving the efficiency of the enterprise in the marketing aspect. At the first stage it is expedient to form the purpose of the project. The second is to develop criteria for the selection and appointment of responsible executors. The third stage involves the definition and implementation of a comprehensive analysis of strategic and current issues to improve the efficiency of the enterprise in the marketing aspect. At the fourth stage, it is advisable to define a strategic goal and its structuring. The fifth stage is the substantiation of the main directions of efficiency increase. At the sixth stage, it is advisable to form alternatives to achieve the goals. At the seventh stage, the financial, personnel, production, innovation, information and communication and marketing costs of the project should be optimized. The eighth stage – the distribution of responsibility for the project between the structural units of the enterprise. In the practical implementation of the developed methodological support there is a real possibility of transition to alternative options for project implementation in the conditions of constant transformations, which contributes to the formation of the economic effect at the macro-, meso- and microeconomic levels.